An Analytical Network Process for Selecting Raw Material Suppliers of UNP100: A Case Study - Ririh, Kirana Rukmayuninda; Ningtyas, Desinta Rahayu; Taufiq Rahman, Fikri (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2021)
A UNP-100 is a canal iron that connects the storage area (bin) to the frame of a truck. Therefore, the selection of UNP-100 suppliers is an essential process. Suppliers are chosen to provide high-quality materials, in-time deliveries, affordable prices, and excellent services, the applied analytical network process (ANP) in this study. The quantitative method is conducted through questionnaires, and the qualitative method is by interviews. After distributing the questionnaires, calculations are carried out to assess suppliers by constructing an ANP supermatrix. The respondents are the purchasing managers, the quality managers, and the PPIC managers. The criteria to choose suitable suppliers are packaging (0.060), price (0.212), customer care (0.712), delivery (0.103), and quality (0.351). The prioritized UNP-100 suppliers are PT. KPPE (0.346), PT. KPS (0.344), and PT. SME (0.31).